(untitled) (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Abstract: The analysis in this article offers a comprehensive study of the acceptance of the cultural model of the black race and its profound influence on the formation of fiction. Through a critical engagement with the intersections of culture, identity, and narrative, this study illuminates the dynamic and evolving nature of black narrative, highlighting its continued relevance and resilience in the field of literature.